The Effect of Supportive Implementation of Healthier Canteen Guidelines on Changes in Dutch School Canteens and Student Purchase Behaviour - Evenhuis, Irma J. (Nutrients, 2020)
We developed an implementation plan including several components to support implementation of the “Guidelines for Healthier Canteens” in Dutch secondary schools. This study evaluated the effect of this plan on changes in the school canteen and on food and drink purchases of students. In a 6 month quasi-experimental study, ten intervention schools (IS) received support implementing the guidelines, and ten control schools (CS) received only the guidelines. Changes in the health level of the cafeteria and vending machines were assessed and described. Effects on self-reported purchase behaviour of students were analysed using mixed logistic regression analyses. IS scored higher on healthier availability in the cafeteria (77.2%) and accessibility (59.0%) compared to CS (60.1%, resp. 50.0%) after the intervention. IS also showed more changes in healthier offers in the cafeteria (range −3 to 57%, mean change 31.4%) and accessibility (range 0 to 50%, mean change 15%) compared to CS (range −9 to 46%, mean change 9.7%; range −30 to 20% mean change 7% resp.). Multi-level logistic regression analyses on the intervention/control and health level of the canteen in relation to purchase behaviour showed no relevant relations. In conclusion, the offered support resulted in healthier canteens. However, there was no direct effect on students’ purchase behaviour during the intervention.